Angels on Earth : inspiring stories of fate, friendship, and the power of connections - Schroff, Laura; Tresniowski, Alex (Howard Books, 2016)
"From the #1 New York Times and international bestselling authors of An Invisible Thread comes a heartwarming and inspiring book about the incredible impact that acts of kindness from strangers can have on the world around us. One day in 1986, Laura Schroff, a busy ad sales executive, passed an eleven-year-old boy panhandling on the street. She stopped and offered to take him to McDonald's for lunch. Twenty years later, at Laura's fiftieth birthday party, Maurice Mazyck gave a toast, thanking Laura for her act of kindness, which ended up changing the course of his life. In that toast, Maurice said that when Laura stopped on that busy street corner all those years ago, God had sent him an angel. Laura's invisible thread journey has deepened her belief that angels--divine and otherwise--are all around us. After An Invisible Thread was published in 2011, readers from around the country and world began sharing with Laura their own stories about how chance encounters with strangers have changed their lives. From a woman who saved a life simply by buying someone a book, to a financier who gave a stranger the greatest gift of all, to a teacher who chose a hug over discipline and changed a lost boy's future--Angels on Earth will introduce a series of remarkable people whose invisible thread stories will move, surprise, and inspire readers. Angels on Earth sheds light on how each of us can live happier, more purposeful lives through sharing acts of kindness"--